β-Hexosaminidases Along the Secretory Pathway of Nicotiana benthamiana Have Distinct Specificities Toward Engineered Helminth N-Glycans on Recombinant Glycoproteins - Alvisi, Nicolò; van Noort, Kim; Dwiani, Sarlita; Geschiere, Nathan; Sukarta, Octavina; Varossieau, Koen; Nguyen, Dieu-Linh; Strasser, Richard; Hokke, Cornelis H.; Schots, Arjen; Wilbers, Ruud H. P. (Frontiers in Plant Science, 2021)
β-N-acetyl-hexosaminidases (or HEXOs) belong to families of enzymes that are widely distributed among all kingdoms of life. HEXOs are involved in the hydrolysis of terminal β-N-acetyl-hexosamine residues (GlcNAc and/or GalNAc) from different oligo- or polysaccharide substrates. In plants, little is known about the biological role of HEXOs, but some are responsible for the truncation of complex N-glycans into paucimannosidic structures. For the plant molecular pharming research field, this undesired processing of N-glycans by HEXOs can interfere with the production of pharmaceutically relevant glycoproteins with tailor-made N-glycans. Recently, pioneering work has shown that helminth glycoproteins with therapeutic value can be efficiently produced in Nicotiana benthamiana plants while simultaneously mimicking their native helminth N-glycan composition. However, efficient 'helminthization' of N-glycans in plants by glyco-engineering is hampered by HEXO activity, in particular when aiming for the synthesis of N-glycans with antennary GalNAcβ1-4GlcNAc (LacdiNAc or LDN). In this study, we cloned novel β-hexosaminidase open reading frames from N. benthamiana and characterized the biochemical activity of these enzymes. We identified HEXO2 and HEXO3, but not HEXO1, as enzymes responsible for the cleavage of antennary GalNAc residues of N-glycans on apoplastic proteins. Furthermore, we reveal that each member of the HEXO family has a distinct specificity for N-glycan substrates, where HEXO2 is a membrane-bound enzyme with strict N-acetyl-galactosaminidase activity. This study is the first report that describes a role for plant HEXOs in processing GalNAc-carrying N-glycans in vivo. The ability of plant HEXOs to process non-endogenous N-glycans, together with their chitinolytic activity, hints towards a role in plant defense against invading pathogens or parasites.